Determinants of Online Islamic Banking Use in Almadinah, Saudi Arabia - Aldarabseh, Wesal Mohammad (MEC-J (Management and Economics Journal), 2020)
The purpose of the study is to examine the frequency of online Islamic banking use among customers in Almadinah city, Saudi Arabia. In addition, determinants that influence the adoption of online banking were also investigated. A total of 319 Islamic banking customers were surveyed using a structured questionnaire. Data were analyzed using the Chi square test and logistic regression analysis. The frequency of online Islamic banking users was 78.6%. Factors that found to influence online banking use were age, quality of provided services and easiness of use.Â  The study findings might provide feedback for the Islamic banking sector in the city to enhance its performance in the highly competitive market.